Evaluating temperature effects on leaching behavior of geogenic arsenic and boron from crushed excavated rocks using shaking and nonshaking batch tests - Tomohiro Kato; Atsushi Takai; Yusuke Iwata; Lincoln W. Gathuka; Takeshi Katsumi (Soils and Foundations, 2023)
The leaching behavior of arsenic and boron is evaluated in this work through two types of excavated rocks with geogenic contaminants under different temperatures. Excavated rocks with geogenic contaminants are expected to be used in embankments with appropriate countermeasures being taken against the risks brought about by geogenic contamination. The leaching behavior might change because of changes in the ground temperature. However, the effects of temperature on the leaching behavior of such rocks have not been well examined. Herein, batch leaching tests at temperatures between 5 and 60 °C were performed under shaking and nonshaking conditions. Mudstone and shale rock were crushed into particles smaller than 2 mm, which were required for the tests. The tests were carried out for durations ranging from 6 h to 15 days because changes in leaching kinetics also require careful evaluation. After conducting the nonshaking tests for 15 days at 40 °C, the mudstone sample leached arsenic and boron at concentrations of approximately 0.7 and 1.0 mg/L, respectively. The arsenic and boron concentrations were about 20 and 40% higher than those of the sample leached at a temperature of 20 °C. Elevated temperatures were seen to increase the leaching kinetics of the toxic elements. For the shale rock sample, the leaching rate for arsenic was 7.7 × 10-2/h at 40 °C, which was about 2.5 times greater than the value at 30 °C. The nonshaking tests showed higher leaching amounts of arsenic and boron than the shaking tests, especially at elevated temperatures. As unrealistic estimations should be avoided, nonshaking tests are suggested. Moreover, nonshaking tests lasting longer than 6 h are necessary due to the relatively slow dissolution of minerals.